Ash disposal - mine fires - environment- an Indian dilemma - Michalski, S. R.; Gray, R. E. (Journal of Nepal Geological Society, 2000)
Coal combustion ash disposal at mine sites may provide a means to deal with the serious problems of coal mine fires, orphaned mined land and coal ash disposal in India. India produces about 70 million metric tons per annum (Mta) of coal ash from the combustion of 320 Mta of domestically produced coal, the average ash content being about 30-35 per cent as opposed to an average ash content of less than 10 per cent in the U.S. In other words, India produces coal ash at about triple the rate of the U.S. Currently, 95 per cent of this ash is sluiced into gigantic slurry ponds, many located near urban areas and consuming vast amounts of premium land. Conversely, the Jharia Coalfield produces about 30 Mta of this ash and also contains the world's largest complex of underground coal mine fires. The fires occupy an aggregate surface area of about 10 square kilometres where the land surface is extremely degraded. Similarly, the Singrauli Coalfield, suffers from the environmental effects of open cast mining, overburden dumps for mine waste and an enormous coal combustion ash disposal problem, which is probably the largest such problem in India. Coal combustion ash haulback to the Jharia and Singrauli Coalfields as well as to other coalfields in India can find beneficial use by: - Controlling mine fires through surface and underground sealing with coal combustion ash, - Filling open-cast mine pits, depressed, and subsided areas, - Filling abandoned underground workings to control ground subsidence, - Reducing ground water flow through mine backfill to retard leaching of acid or metals forming constituents, and - Serving as a soil amendment to restore soil fertility. Placement of ash in surface and underground mines whether in the Jharia or Singrauli Coalfields or elsewhere in India, can provide an efficient, cost-effective method to remove significant quantities of ash from pond disposal while at the same time contributing to mine fire and subsidence abatement, mined land reclamation and restoration of land productivity. Wise natural resource management suggests a reasonable approach to disposal and beneficial use of coal ash is to return it to its original location – the mine.